DESEMPEÑO LABORAL DE LOS EMPLEADOS DE LAS FARMACIAS ECONOMICAS DE BABAHOYO - Coll Velasco, Damaris Daniela (2018)
The economic pharmacies were born based on the needs of the population that lacked health, before the increase in the sale of generics grew considerably in the Babahoyo Canton to see a dissatisfied market in the medicinal field, the main objective of which is to help customers and meet their needs